Research progress of IGF‐1 and cerebral ischemia. Issue 1 (28th March 2021) - Li, Shun‐Lian; Li, Jing; Zhou, Hong‐Su; Xiong, Liu‐Lin
Abstract : Cerebral ischemic disease is a group of diseases that cause insufficient blood supply to the cerebrum, cerebellum or brain stem for different reasons, resulting in corresponding nervous system symptoms. Cardiovascular disease is the leading cause of death in the world. Among them, the death caused by cerebral ischemia accounts for the vast majority, and it is one of the fatal diseases in the middle‐aged and elderly at present. Epidemiologic studies have projected increasing mortality due to cardiovascular disease worldwide (about 23.3 million people by 2030) because of the aging population. However, related studies have shown that insulin‐like growth factor I (IGF‐1) is a multifunctional cell proliferation regulator. It plays an important role in cerebral ischemia. It is effective in promoting cell differentiation, proliferation and individual development. Studies have shown that IGF‐1 signaling pathway is a key pathway controlling cell growth and survival. There may be five mechanisms in cerebral ischemia: prevention of intracellular calcium overload, inhibition of the upregulation of nNOS, IGF‐1upregulations activating HIF‐1α, regulation of Bcl‐2 to resist apoptosis, and enhancement of vascular endothelial function. Three critical nodes in the IGF‐1 signaling pathway have been described in cardiomyocytes: protein kinase Akt/mammalian target of rapamycin (mTOR), Ras/Raf/extracellular signal‐regulated kinase (ERK), and phospholipase C (PLC)/inositol 1, 4, 5‐triphosphate (InsP3)/Ca 2+ . IGF‐1 plays an important role in cerebral ischemia and myocardial ischemia, mainly by activating downstream of IGF‐1, controlling cell death and differentiation or transcription work, improving the function of heart muscle cells, reducing the myocardial cell apoptosis induced by myocardial infarction, regulating endogenous protection and restoration of cerebral ischemia injury, thus protecting cerebral and myocardial injury. Related studies have shown that bcl‐2 exerts great influence on both cerebral ischemia and myocardial ischemia. Therefore, the relevant pathways and targets of cerebral ischemia and myocardial ischemia and the role of IGF‐1 in protecting the heart are reviewed in this paper.